PENGARUH PELAKSANAAN PEMBELAJARAN FIQH TERHADAP KEDISIPLINAN SHALAT PADA SANTRI-SANTRIWATI KELAS VII MTs PP TARBIYAH ISLAMIYAH KENEGERIAN KOPAH - Yulia Nengsi; Ikrima Mailani; Alhairi Alhairi (Universitas Islam Kuantan Singingi, 2023)
Fiqh is one of the fields of science in islamic law that specifically discusses legal issues. Based on the above background, this study aims to determine whether there is any effect of the implementation of fiqh learning on the prayer discipline of the prayer discipline of the seventh grade student. This research is a causal associative quantitative. The date collection technique used is a questionnaire with an instrument in the form of a questionnaire as primary data.. Data analysis using a simple linear regression formula which is then processed using the SPSS 20.0 software. The results of this study indicate that the t-count value is -1.936 which is smaller than the t-table value of 1,999. This can also be seen in the significanse value (Sig) which is 101 greater than the probality of 0,05 or 101>0,05. And seen from the value of the coefficient of determination (R Square) of 0,384 or if the percentage is 38,4% it can be concluded that there is no effect of the implementation of fiqh learning on the prayer discipline of class VII MTs PP Tarbiyah Islamiyah Kenegerian Kopah